A comparative account of the seasonal variation of circulating blood cells of toad, Bufo melanostictus and wall lizard, Hemidactylus flaviviridis (University Journal of Zoology, Rajshahi University, 2007)
Key words: Circulating blood; total count; differential count; B. melanostictus; H. flaviviridis Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 39-42